Response to Comments on E. Huttunen-Saarivirta et al., "Kinetic Properties of the Passive Film on Copper in the Presence of Sulfate-Reducing Bacteria" [J. Electrochem. Soc., 165, C450 (2018)]. Issue 10 (10th June 2019) - Huttunen-Saarivirta, E.; Rajala, P.; Carpén, L.; Wang, J.; Liu, F.; Ghanbari, E.; Mao, F.; Dong, C.; Yang, J.; Sharifi-Asl, S.; Macdonald, D. D.
Abstract : The Comments by Martino et al. 1 on the original manuscript 2 criticize our interpretation of the existence and properties of the Cu2 S barrier layer of the passive film that forms on the surface of copper in SRB-bearing groundwater at 10°C. First, it is necessary to recognize that this discussion involves two forms of copper, which we refer to as "pure copper (P-Cu)" (nominally > 99.999%) and "oxygen-free phosphorous copper (OFP-Cu)". P-Cu has been used in the majority of our work 3 –6 with only some of our later work employing OFP-Cu, 2 a point that does not seem to be appreciated by Martino et al. 1 On the other hand, the Shoesmith group appears to have concentrated exclusively upon OFP-Cu, at least in recent years. 7 –11 This difference is of crucial importance in responding to the critique by Martino et al. 1